2020
DOI: 10.1101/2020.06.17.20133942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toward patient-centered tuberculosis preventive treatment: preferences for regimens and formulations in Lima, Peru

Abstract: Background: To ensure patient-centered TB preventive treatment, it is important to consider factors that make it easier for patients to complete treatment. However, there is little published literature about patient preferences for different preventive treatment regimen options, particularly from countries with high tuberculosis burdens. Methods: We conducted a qualitative research study using a framework analysis approach to understand preventive treatment preferences among household contacts. We conducted … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Other studies have found this to be true, specifically in the context of TB treatment [ 28 , 29 ]. The higher treatment completion among older contacts may be due to the difficulty of administering pills to young children [ 30 , 31 ], as pediatric formulations of isoniazid are not available in Peru. Greater autonomy of adolescent contacts and less reliance on caregivers may have also contributed to this result.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found this to be true, specifically in the context of TB treatment [ 28 , 29 ]. The higher treatment completion among older contacts may be due to the difficulty of administering pills to young children [ 30 , 31 ], as pediatric formulations of isoniazid are not available in Peru. Greater autonomy of adolescent contacts and less reliance on caregivers may have also contributed to this result.…”
Section: Discussionmentioning
confidence: 99%
“…Study participants in Peru preferred the 3-month weekly rifapentine plus isoniazid (3HP) regimen as it was easier to remember and less disruptive of everyday life. However, caregivers favoured a child-friendly regimen of syrups or dispersible tablets above the shorter treatment duration, which highlights the need to prioritize access to a child-friendly formulation of rifapentine [17 ▪ ]. Ongoing and upcoming studies investigating the use of 3HP in children, which importantly include those less than 2 years [TB Clinical Trials Consortium Study (TBTC) 35] [18] and 1-month daily rifapentine and isoniazid in children (IMPAACT 2024) [19] will provide additional evidence on the dosing, safety and acceptability of these regimens and inform options available to young household contacts.…”
Section: Tuberculosis Preventionmentioning
confidence: 99%